Strategies for Identification of Intimate Partner Violence in Healthcare Settings: Overview of Reviews and Realist Synthesis - Melendez-Torres, G. J. (Journal of family violence, 2023)
Purpose Healthcare settings remain important contexts for the identification of intimate partner violence (IPV); however, identification strategies for IPV are diverse and work in complex ways that may differ across contexts. To understand how, rather than if, IPV identification strategies work, we undertook a systematic review of reviews with realist synthesis.MethodsWe undertook a search of five databases for full-text, peer-reviewed systematic reviews addressing identification strategies for IPV in healthcare contexts. We screened titles and full texts in duplicate and independently, appraised included systematic reviews and synthesized them using methods from realist synthesis to develop context-mechanism-outcome configurations (CMOCs).ResultsWe included 29 reviews reported in 32 publications. Our findings were summarized in four CMOCs at system, system–clinician, clinician and patient levels. CMOCs underscored the role of supportive clinical and practice contexts, patient-provider relationships and continuity of care to ensure the benefits, and reduce the potential harms, of a range of identification strategies. CMOCs also highlighted the importance of supporting clinicians through clinical policies and protocols to ensure a consistent, safe and effective response to IPV.ConclusionsFuture work should address how supportive clinical contexts that facilitate effective inquiry, disclosure, and referral to services can be created, acknowledging that what works in one context may not work in another. Included systematic reviews did not permit exploration of how racial and ethnic diversity relate to identification strategies. This is an area requiring urgent research to inform clinical practice.